Nanoparticles in Photodynamic Therapy - Thomas Nann (Nano Biomedicine and Engineering, 2011)
This article contains a critical review on the application of different types of nanoparticles in photodynamic therapy (PDT). Passive carrier particles like photosensitiser-“doped” silica nanoparticles are discussed as well as luminescent and noble metal nanocrystals in conjunction with molecular photosensitisers. Recent achievements are highlighted and the fundamental limitations of these systems are discussed. The article is concluded by an outlook on potential improvements and the possibility for practical applications of nanoparticle-based PDT.